METAFORA DALAM KUMPULAN PUISI KERTAS BASAH KARYA DEA ANUGRAH - Safitri, Indah; Harjito, Harjito; Septiana, Ika (Jurnal Bahastra, 2023)
This study aims to describe the forms of figurative language used in Dea Anugrah's Wet Paper poetry. This research uses descriptive analysis method. Data collection uses the technique of observing and noting. Before conducting the research, the first step is reading a collection of Wet Paper poems by Dea Anugrah to find out the style of metaphorical language contained in the poem, then the second step is to record the results of the language style contained in the metaphorical language style in Dea Anugrah's Wet Paper poetry, and after that describe or analyze the meaning. the appropriate metaphorical language style in the Wet Paper poem by Dea Anugrah. The results of the analysis of the research on metaphorical figurative language in the poetry of Kertas Wet by Dea Anugrah are 20 styles of metaphorical language from 13 collections of Kertas Wet poems by Dea Anugrah. This study aims to describe the forms of figurative language used in Dea Anugrah's Wet Paper poetry. This research uses descriptive analysis method. Data collection uses the technique of observing and noting. Before conducting the research, the first step is reading a collection of Wet Paper poems by Dea Anugrah to find out the style of metaphorical language contained in the poem, then the second step is to record the results of the language style contained in the metaphorical language style in Dea Anugrah's Wet Paper poetry, and after that describe or analyze the meaning. the appropriate metaphorical language style in the Wet Paper poem by Dea Anugrah. The results of the analysis of the research on metaphorical figurative language in the poetry of Kertas Wet by Dea Anugrah are 20 styles of metaphorical language from 13 collections of Kertas Wet poems by Dea Anugrah.